1979
DOI: 10.7883/yoken1952.32.337
|View full text |Cite
|
Sign up to set email alerts
|

Antigenic Analysis by Direct Immunofluorescence of 114 Isolates of Rickettsia Tsutsugamushi Recovered From Febrile Patients in Rural Malaysia

Abstract: SUMMARY: One hundred and fourteen Rickettsia tsutsugamushi isolates , re covered from febrile patients in central Peninsular Malaysia , were antigenically analyzed by direct immunofluorescence using eight prototype strains . Twenty-nine antigenic types were detected. The TA763 , TA716, Karp and TA686 strains were the most common and occurred singly or in combination with each other or other strains in 86% of the isolates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
37
1

Year Published

1980
1980
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 10 publications
2
37
1
Order By: Relevance
“…The study in the Bukit Mendi oil palm complex has demonstrated the predominance of Karp and Karp-related antigens in rodent isolates. These findings correlate with those found in the study with human isolates from the same sera (Shirai et al, 1979). Additionally, the analysis of R. tsutsugamushi organisms identified in infected chiggers from the same area showed the presence of only Karp and Karp-related strains (unpublished data).…”
supporting
confidence: 87%
See 2 more Smart Citations
“…The study in the Bukit Mendi oil palm complex has demonstrated the predominance of Karp and Karp-related antigens in rodent isolates. These findings correlate with those found in the study with human isolates from the same sera (Shirai et al, 1979). Additionally, the analysis of R. tsutsugamushi organisms identified in infected chiggers from the same area showed the presence of only Karp and Karp-related strains (unpublished data).…”
supporting
confidence: 87%
“…Since rodents are common in these areas and serve as the primary hosts for the vector chiggers, the study afforded an opportunity to examine the relationship between strains existing in nature and those causing human infections. The human Rickettsia tsutsugamushi isolates from Bukit Mendi have been antigenically analyzed (Shirai et al, 1979). This report presents data on the isolates from rodents collected within the Bukit Mendi complex.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although isolates with multiple antigenic combinations could result from a single rickettsial strain with a mosaic of determinants, we believe the most obvious explanation is that these represent mixtures of individual strains. A similar conclusion was reached in a recent study with two Leptotrombidium species of laboratory-reared chiggers which were multiplyinfected with R. tsutsugamushi strains (Shirai et al, 1982b (Shirai et al, 1978(Shirai et al, , 1979(Shirai et al, , 1980(Shirai et al, , 1981a(Shirai et al, ,b,c, 1982a …”
supporting
confidence: 78%
“…Of the 42 isolates studied, 23 were from organ suspensions from individual rodents, and the rest were from organ pools of 2 to 11 animals. The serologic analyses of the isolates were performed by direct immunofluorescence, using the eight prototype strains of R. tsutsugamushi: Karp, Gilliam, Kato, TA678, TA686, TA716, TA763 and TH 1817 (Shirai et al, 1979). Table I summarizes the antigenic characterization of the isolates from the Pescadores Islands.…”
mentioning
confidence: 99%